Biodiversity monitoring in bamboo coral assemblages in the North Aegean Sea, eastern Mediterranean Basin - Chrysoula Gubili; Konstantinos Touloumis; Esprit Saucier; Aristeidis Christidis; Elina Samara; Paraskevi Papadopoulou; Stelios Triantafillidis; Nikolaos Kamidis; Emmanouil Koutrakis (Biodiversity Data Journal)
Deep-sea bamboo coral assemblages are often undescribed in the eastern Mediterranean Sea. Their structural complexity provides essential habitats for many species and promotes high biodiversity that is poorly known. In this study, we examined the effects of coral presence on biodiversity of benthic communities from a scientific trawl survey in the North Aegean Sea carried out in 2018. Genetic analyses did not support the first species identification of the coral as Isidella elongata (Esper, 1788). All searches resulted in matches belonging to Acanella specimens, a genus with a disputed taxonomic validity since its initial description. Quantitative data from macrobenthos in coral assemblages revealed the presence of at least 45 species. Additionally, few species of economic importance were exclusively detected in the haul associated with coral assemblages, which also hosted the highest species richness. Our results highlight the importance of such ecosystems as diversity hotspots in the marine environment, which are heavily impacted by human activities and are extremely important to commercial fisheries.